The Comprehensive Systematic Review of Readmission Rates for Patients with Pleural Effusion - Ian Aji Prahasta; Tika Indriati; Lydia Arieta (International Medical Journal Corp. Ltd, 2026)
Introduction: Pleural effusion is a common clinical condition associated with significant healthcare burden, yet readmission rates and their determinants remain poorly characterized across different etiologies. This systematic review synthesizes evidence on readmission rates, risk factors, treatment interventions, and clinical outcomes in adult patients with pleural effusion. Methods: A systematic review was conducted using rigorous screening criteria including studies reporting readmission outcomes in adult pleural effusion patients. Data were extracted on patient populations, readmission rates, risk factors, readmission characteristics, interventions, clinical outcomes, and study design. A total of 111 studies published were included, comprising retrospective and prospective cohort studies, database analyses, and interventional trials. Results: Thirty-day all-cause readmission rates ranged from 20.7-38.3% for malignant pleural effusion (MPE), 1.4-20.8% for trauma-related effusions, 9.1-12.5% for post-cardiac surgery, and 10.5-35.9% for heart failure. Pleural effusion was the direct cause of readmission in 24.3-69.5% of MPE cases. Key risk factors included older age, multiple comorbidities, thoracentesis-only management (vs definitive procedures), presence of effusion at discharge, and discharge to care facilities. Definitive procedures (indwelling pleural catheters, pleurodesis) significantly reduced readmissions compared to serial thoracentesis (p<0.001). System-level interventions including specialized pleural clinics and multidisciplinary pathways reduced hospital admissions by 24-47%. Readmission was associated with substantially increased mortality (17-20% for MPE) and healthcare costs (>15,000 per readmission). Discussion: This review identifies significant heterogeneity in readmission rates across effusion etiologies and demonstrates that readmissions are frequently preventable through definitive management strategies and coordinated care models. The evidence strongly supports transitioning from reactive, repetitive drainage to proactive, definitive interventions and systematic care pathways. Conclusion: Readmission in pleural effusion patients is common, costly, and associated with poor outcomes. Implementation of definitive procedures and specialized pleural services represents evidence-based strategies to reduce readmission burden. Future research should focus on prospective validation of risk prediction models and comparative effectiveness of definitive interventions across diverse populations.